Influence of the Great Amazon Reef System and Pleistocene sea-level drops on the phylogeography of Haemulon aurolineatum (Haemulidae) - Awhida-Robinson, A. Karim; Torres-Hernández, Eloísa; Pérez-Rodríguez, Rodolfo; Piñeros, Víctor Julio; Solís-Guzmán, María Gloria; Angulo, Arturo; Simões, Nuno; Lasso-Alcalá, Oscar M.; Monroy, Mario; Domínguez-Domínguez, Omar (PeerJ, 2025)
Background Phylogeography is based on the principle that species exhibit genetic structure shaped by biogeographic, ecological or environmental barriers, using both genetic and geographic components, offering valuable insights into evolutionary processes. In marine organisms, gene structure is influenced by life histories, geological events, and oceanographic conditions. The Greater Caribbean (GC), is a biogeographic region spanning from North Carolina, United States to northern Guyana, comprising three provinces: Northern, Central and Southern Caribbean. South of the GC is the Brazilian biogeographic province. Bellow the Amazonas-Orinoco plume the Great Amazon Reef System is present having mesophotic reefs situated beneath the freshwater discharge of the river. Each province is defined by distinct oceanographic conditions and habitat types, which play a significant role in shaping the evolutionary history of fish species. Due to its life history traits and the habitat heterogeneity across the GC, Haemulon aurolineatum, a widespread species found from Chesapeake Bay to Southern Brazil serves as an excellent model for studying evolutionary history of reef fishes in the GC region. Methods We use three nuclear DNA (nDNA) and one mitochondrial DNA (mtDNA) markers to study the phylogeographic history of H. aurolineatum. We performed gene structure, diversity indexes, haplotype networks, isolation by distance test, divergence time analysis and species delimitation methods in populations distributed through the geographic range of the species to understand the relation between the evolutionary history of the species, geophysical and biological aspects and make some taxonomic annotations. Results All four molecular markers revealed two distinct genetic groups: one predominantly distributed in the Northern province and the other mainly found in the Central, Southern Caribbean and Brazilian provinces. The divergence between these groups is estimated to have occurred around 800,000 years ago (Kya), this is attributed to the redirection of the Loop Current caused by climatic and oceanographic changes during the Pleistocene epoch. Our investigation has found genetic homogeneity among populations in the Central, Southern, and Brazilian provinces, which may be attributed to the ability of H. aurolineatum to migrate along the mesophotic reefs of the Great Amazon Reef System within the Amazonas-Orinoco plume region.
Keywords: Genetic structure; Geographic barrier; Mesophotic reefs; Tomtate grunt; Greater Caribbean